Identification and characterization of major cat allergen Fel d 1 mimotopes on filamentous phage carriers. (March 2016) - Luzar, Jernej; Molek, Peter; Šilar, Mira; Korošec, Peter; Košnik, Mitja; Štrukelj, Borut; Lunder, Mojca
Highlights: Peptide mimotopes of cat allergen Fel d 1 were identified through immunoscreening. Phage carriers with multiple copies of an individual mimotope were constructed. Mimotopes were reactive to IgE from cat-allergic patients sera. They showed no basophil activation of the corresponding cat-allergic patients. Mimotopes on carriers are good candidates for development of hypoallergenic vaccine. Abstract: Cat allergy is one of the most prevalent allergies worldwide and can lead to the development of rhinitis and asthma. Thus far, only allergen extracts from natural sources have been used for allergen-specific immunotherapy. However, extracts and whole allergens in immunotherapy present an anaphylaxis risk. Identification of allergen epitopes or mimotopes has an important role in development of safe and effective allergen-specific immunotherapy. Moreover, with a suitable immunogenic carrier, the absence of sufficient immune response elicited by short peptides could be surmounted. In this study, we identified five structural mimotopes of the major cat allergen Fel d 1 by immunoscreening with random peptide phage libraries. The mimotopes were computationally mapped to the allergen surface, and their IgE reactivity was confirmed using sera from cat-allergic patients. Importantly, the mimotopes showed no basophil activation of the corresponding cat-allergic patients, which makes them good candidates for the development of hypoallergenic vaccine. As bacteriophage particles are becoming increasingly recognized as immunogenic carriers, we constructed bacteriophage particles displaying multiple copies of each selected mimotope on major phage coat protein. These constructed phages elicited T cell-mediated immune response, which was predominated by the type 1 T cell response. Mimotopes alone contributed to the type 1 T cell response by promoting IL-2 production. Fel d 1 mimotopes, as well as their filamentous phage immunogenic carriers, represent promising candidates in the development of hypoallergenic vaccine against cat allergy.